A survey of East Palaearctic Gnaphosidae (Aranei). 9. New data on the Parasyrisca potanini-group from Central Asia - Fomichev AA; Marusik YM; Sidorov VV (KMK SCIENTIFIC PRESS LTD, MOSCOW STATE UNIV, 2022)
Both sexes of three new species of Parasyriscaare described from Eastern Kazakhstan and Western Mongolia: P. kosachevi sp.n., P. sulaki sp.n., and P. tronovorum sp.n. All new species were collected in highlands at elevations from 2700 to 3700 m. The female of P. volynkini Fomichev, 2016 from the Altai Mountains (South Siberia, Russia) is described for the first time. Descriptions, differential diagnoses, illustrations, and maps of distribution records are provided. The distribution and species composition of the all four Parasyrisca groups (potanini, vinosa, guzeripli, and breviceps) are discussed.